AWARENESS ABOUT CHILDHOOD AUTISM AMONG RESIDENT PHYSICIANS OF SURGICAL, NONSURGICAL AND FIRST-CONTACT DISCIPLINES (FAMILY MEDICINE+ PEDIATRICS+ OTORHINOLARYNGOLOGY) OF A RESEARCH AND TRAINING HOSPITAL IN ISTANBUL, TURKEY - (:unkn) unknown (ISTANBUL UNIV, FAC MEDICINE, PUBL OFF, 2020)
Objective: The objective of this descriptive study was to assess the awareness of childhood autism among 275 physicians undergoing their residency training in several disciplines which were classified as surgical, nonsurgical and first-contact disciplines (Family medicine + Pediatrics + Otorhinolaryngology) of a Research and Training Hospital in Istanbul, Turkey. Material and Method: Data were collected through a self-administered questionnaire. Residents scoring below 20 were considered as low scoring; and residents scoring 20 and above were considered as high scoring; Chi-square test and Fisher's chi-square test were applied for finding association between categorical variables. Results: The characteristics of childhood autism emerging with statistically significant differences between the disciplines (p<0.05) were a child with autism frequently has repetitive and stereotypical behaviours and about the outstanding talents a child with autism might have. Around 94.1% of the first-contact disciplines and 93.3% of the nonsurgical disciplines were in the high-scoring group; whereas 82.6% of the surgical disciplines could be placed in the high-scoring group. This difference was statistically significant (p <0.05). Conclusion: In this study, the physicians undergoing their residency training in the first-contact disciplines, namely Family Medicine + Pediatrics + Otorhinolaryngology, were found to be more knowledgeable on childhood autism as compared to the ones undergoing residency training in the surgical disciplines. This was considered as a pleasing finding since the first-contact disciplines are most likely to be in an initial position to detect a child with autism in the community, refer him/her to the health authorities and continue monitoring him/her from thereon.
Keywords: Childhood autism; awareness; resident physicians; non-surgical disciplines; SPECTRUM DISORDER; KNOWLEDGE; CHILDREN; DIAGNOSIS